Chitin and Chitosan. Part II. Applications of chitosan. - Marcin H. Struszczyk (Polimery)
A review covering 131 refs. shows the applications of chitosan,i.e., in water treatment, pulp and paper, medical and pharmaceutical materials, cosmetics, biotechnology, agriculture, food and feed additives, textile and membranes. Attention was focused on use of chitosan in papermaking. Commercial chitosan was described, with its various application forms [microcrystalline (MCCh), beads and membranes, chitosan fibres and textile containing chitosan].